2021
DOI: 10.1073/pnas.2020635118
|View full text |Cite
|
Sign up to set email alerts
|

Functional monovalency amplifies the pathogenicity of anti-MuSK IgG4 in myasthenia gravis

Abstract: Human immunoglobulin (Ig) G4 usually displays antiinflammatory activity, and observations of IgG4 autoantibodies causing severe autoimmune disorders are therefore poorly understood. In blood, IgG4 naturally engages in a stochastic process termed “Fab-arm exchange” in which unrelated IgG4s exchange half-molecules continuously. The resulting IgG4 antibodies are composed of two different binding sites, thereby acquiring monovalent binding and inability to cross-link for each antigen recognized. Here, we demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 56 publications
1
40
1
Order By: Relevance
“…A more pronounced and longstanding response to RTX-induced B-cell depletion was observed in MuSK-MG, refractory to traditional therapies: it involves the circuit of specific anti-MuSK IgG4 as we previously demonstrated by the paralleled prolonged reduction of specific IgG4 MuSK antibodies [9]. Since most of pathogenetic MuSK IgG4 consists in hybrid molecules, our results could be very useful for a better selection of MuSK-MG pts to be treated with RTX [11][12][13].…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…A more pronounced and longstanding response to RTX-induced B-cell depletion was observed in MuSK-MG, refractory to traditional therapies: it involves the circuit of specific anti-MuSK IgG4 as we previously demonstrated by the paralleled prolonged reduction of specific IgG4 MuSK antibodies [9]. Since most of pathogenetic MuSK IgG4 consists in hybrid molecules, our results could be very useful for a better selection of MuSK-MG pts to be treated with RTX [11][12][13].…”
Section: Discussionsupporting
confidence: 53%
“…However, MuSK-MG does not fulfill IgG4-RD criteria, even if a recent case report opens a new scenario on a putative link between the two diseases [16]. In recent years, it has been well demonstrated that a considerable proportion of MuSK IgG4 is Fab-arm exchanged without affecting pathogenetic mechanisms of disease [11][12][13].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations